Media framework of Israeli propaganda on facebook: an analytical study for the official page of ’ Israeli Defence Force’ spokesperson - Oreqat, Ahmad; Al-Kharabsheh, Mohammed (Jordan Journal of Social Sciences, 2021)
This study aimed to identify the media framework for the Israeli propaganda on Facebook. The study used the descriptive approach and the method of content analysis by means of the content analysis form from 1/1/2018 to 25/3/2018. The results of the study came in the category of strategic framework ranked first in the publications of the spokesman of the Israeli army, 36.966% and the category of media sources has replaced the category of reliance on him as a source in the first place by (25.555%). The local geographical area category is superior to the category of regional and international domains by 65.534%. In the categories of attachments used, Of 65.181% The percentage of the percentage of responses was a strong percentage in the first place with 55.567%, and the rate of reaction rate (comments) came strong category by 39.603%.